ANALISIS EFEKTIFITAS PROGRAM CORPORATE SOCIAL RESPONSIBILITY PT.AMNT DI KECAMATAN SEKONGKANG, SUMBAWA BARAT - SYARAFUDIN SYARAFUDIN; UMAR UMAR; SHINTA ESHABELLA (Universitas Mahasaraswati K. Mataram, 2023)
The aims of this research are; 1) to determine the communication strategy of PT.AMNT's CSR program in Sekongkang subdistrict, West Sumbawa Regency, 2) to identify the quality of stakeholder responses to PT's corporate branding or image. AMNT, and 3) analyzing the effectiveness of PT.AMNT's CSR program in Sekongkang sub-district, West Sumbawa Regency according to stakeholders.The design of this research is Mixed Method or mixed research which combines qualitative analysis with quantitative analysis. The sample for this research consisted of 175 people consisting of 25 people in each village in Sekongkang sub-district. CSR program communication strategy data was collected through in-depth interviews, data on stakeholder responses to corporate branding was collected through interviews and questionnaires, while CSR program effectiveness data was collected through questionnaires which were then analyzed using a 5 Likert scale.The results of the research show that the communication strategy of PT.AMNT's CSR program in Sekongkang sub-district has fulfilled the ten elements of the established communication strategy and has successfully implemented information stakeholder strategy, response stakeholder strategy, and involvement stakeholder strategy. According to the majority (>88%) of stakeholders in Sekongkang sub-district, agree that PT.AMNT has a good CSR program. Stakeholders in Sekongkang sub-district also have the view that PT.AMNT has effective CSR programs. After conducting a correlation test using the Pearson test, the r_count value (0.844) was greater than r_table (0.354) and the r_count value was close to one, so it can be concluded that PT AMNT's CSR program is effective in Sekongkang sub-district and has a strong correlation with the company's corporate branding.